The Development of Small Molecule Inhibitors of Glutaminyl Cyclase and Isoglutaminyl Cyclase for Alzheimer's Disease. Issue 35 (19th September 2019) - Xu, Ana; He, Feng; Yu, Chenggong; Qu, Ying; Zhang, Qiuqiong; Lv, Jiahui; Zhang, Xiangna; Ran, Yingying; Wei, Chao; Wu, Jingde
Abstract: Alzheimer's disease (AD), a common form of dementia, is a progressive neurodegenerative disease and one of the leading causes of death in the elderly worldwide. The exact underlying pathogenesis of AD remains elusive because of its complexity and involvement of multiple factors. Glutaminyl cyclase (QC) and isoGlutaminyl cyclase (isoQC) belong to the family of the metalloenzymes and catalyze the intramolecular cyclization of N‐terminal L‐glutamine/glutamate residues of certain proteins into pyroglutamic acid (pGlu). The amyloid protein and the monocyte chemoattractant protein (MCP‐1) also known as CCL2 that promotes a cascade of inflammation‐related responses are two representative substrates. Moreover, it has been demonstrated that the pyroglutamated Aβ and CCL2 exhibit more severe neurotoxicity than normal Aβ and CCL2. Thus, QC represents one of the attractive targets to develop novel treatments for AD. In this review the recent development of QC inhibitors as anti‐AD agents will be summarized. Abstract : Glutaminyl cyclase (QC) and isoGlutaminyl cyclase (isoQC) are two metalloenzyme that catalyzes the intramolecular cyclization of Aβ‐N‐terminal glutamine and CCL2 into pyroglutamic acid (pGlu) exhibiting more severe neurotoxicity than normal Aβ and CCL2. Both pGlu‐ modified Aβ‐peptides and pE‐CCL2 are discussed to be the crucial species involved in the early onset of AD. So far, most of QC inhibitors have demonstrated a sub‐ or low micromolar IC50 . QC represents a novel target for the development of AD treatments.